Mathematical simulation of moisture evaporation from forest fuel based on conductive model with movable front of phase transition; International Conference on Thermal Analysis and Calorimetry in Russia (RTAC-2016); Vol. 1 - Baranovskiy N. V. Nikolay Viktorovich (Section 2: Thermal analysis and calorimetry of organic substances and materials, 2016)
Basic mathematical model of forest fue l layer drying taking into account dynamics of movement of moisture evaporation front movement in vertical direction of surface ground cover is presented. Mathematically forest fuel layer drying process is described by system of the nonstationary partial differential equation of parabolic type with corresponding initial and boundary conditions. Results of numerical research of forest fuel layer drying under the influence of radiant thermal flux from forest fire front are presented. The analysis of the mechanism and laws of moisture evaporation from surface ground cover is carried out.